Post-automation - Smith, Adrian (2021)
Tremendous research, policy, and investment is directed towards a new wave of automation in modern societies. Most notable within discourse for the Fourth Industrial Revolution, but also in radical ideas for Fully Automated Luxury Communism, automation appears essential to the future. Advocates claim it will renew capital accumulation, boost labour productivity, and extend managerial control in sustainable systems of production and consumption. Noting criticism about future essentialism in this automation advocacy, this essay will turn to innovations in marginal industrious spaces within industrial societies. Here people are hacking, subverting and appropriating ostensibly automating technologies for purposes of creativity, collaboration, and care. Social capabilities in post-automation are being cultivated. Perhaps greater attention to the politics implied in post-automation can help open our futures to more democratic deliberation?